The Effect of Anthelmintic Treatment on Coccidia Oocyst Shedding in a Wild Mammal Host with Intermittent Cestode Infection - Radovan Václav; Jana Blažeková (The Scientific World Journal)
While hosts are routinely exploited by a community of parasite species, the principles governing host responses towards parasites are unclear. Identifying the health outcomes of coinfections involving helminth macroparasites and microparasites is one area of importance for public and domestic animal health. For instance, it is controversial how deworming programmes affect incidence and severity of such important microparasite diseases as malaria. One problem is that most study systems involve domestic and laboratory animals with conditions hardly comparable to those of free-living animals. Here, we study the effect of anthelmintic treatment on coccidia infection intensity in wild Alpine marmots, M. marmota. Our results lend support to the hypothesis that helminth infection has a positive effect on concurrent microparasite infection. However, our work also points to the fact that within-host interactions between helminths and microparasites are context-dependent and can turn to negative ones once helminth burdens increase. Our study suggests that coccidia benefit from intermittent helminth infection in marmots due to the protective effects of helminth infection only during the early phase of the host’s active season. Also, the marmot’s response towards coccidia infection appears optimal only under no helminth infection when the host immune response towards coccidia would not be compromised, thereby pointing to the importance of regular intestinal helminth elimination by marmots just before hibernation.